Optimizing the Performance of different Airfoils at Various Angles of Attack through CFD Simulation - Ghulam , Kazim; Ali, Faizan; Khan Gorar, Athar Ali (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study specifically examines the NACA 0012, NACA 4412, and NACA 2412 airfoil profiles using ANSYS FLUENT. By simulating the flow over these airfoils, we can comprehensively explore the impact of the angle of attack on lift and drag coefficients. Notably, the study reveals that the angle of attack directly influences lift force, with a critical angle beyond which the aircraft may stall. Thus, the research underscores the importance of maintaining an optimal angle of attack to avoid turbulence and optimize aircraft performance. The aerodynamics of airfoil shapes play a crucial role in the performance and safety of aircraft. Understanding airflow characteristics over airfoils, particularly concerning the critical angle of attack, is paramount in achieving optimal lift while avoiding stalling. This paper delves into the shift of the separation point on the upper surface of most airfoil shapes, emphasizing the shift from the trailing edge to the leading edge as the angle of attack increases. Stalling becomes a critical concern beyond the critical angle of attack, necessitating comprehensive research to enhance aircraft performance and safety.
Keywords: Airfoil; Angle of Attack; Lift Coefficient; Drag Coefficient; Simulation Techniques; Turbulence Model; NACA Profiles